Antibody Response to Plasmodium Vivax Antigens in Fy-Negative Individuals From the Colombian Pacific Coast (2005)
ABSTRACT: The Duffy antigen (Fy) is necessary for Plasmodium vivax invasion of human erythrocytes. Some populations have a highly prevalent Fy-negative phenotype; such persons are naturally protected from P. vivax blood infection but are expected to completely support the P. vivax pre-erythrocytic cycle, representing a valuable model for studying the immune response during these parasitic stages. We typed 214 individuals, mostly Afro-Colombians, from a P. vivax-endemic area for Fy expression and determined the antibody response to P. vivax pre-erythrocytic (sporozoites and CS) and blood-stage antigens (blood forms, P. vivax merozoite surface protein 1, and P. vivax Duffy binding protein [PvDBP]). Antibody titers to P. vivax circumsporozoite protein, P11, and N-terminal peptides and the number of responders were similar in Fy-negative and Fy-positive individuals. The number of responders to sporozoites, blood forms, and PvDBP were different between these groups. Thus, Fy-negative individuals from malaria-endemic areas can be used to study the immune response to the P. vivax liver phase without interference of the erythrocytic cycle